Altered Range of Motion and Plantar Pressure in Anterior and Posterior Malaligned Total Ankle Arthroplasty: A Cadaveric Gait Study. (18th September 2019) - McKearney, Daniel A.; Stender, Christina J.; Cook, Brian K.; Moore, Erik S.; Gunnell, Lea M.; Monier, Bryan C.; Sangeorzan, Bruce J.; Ledoux, William R.
Abstract : Background: Malaligned ankle arthroplasty components have been associated with increased postoperative pain and reduced ankle range of motion. With this study, we aimed to quantify how anterior and posterior malalignment of the talar component affects foot bone kinematics and plantar pressures in a dynamic, cadaveric gait simulation. Methods: Ten cadaveric foot specimens received a modified ankle prosthesis. Proper alignment was defined as the prosthesis being neutral to a plantigrade foot, where varus/valgus and internal/external rotation were determined using the tibial alignment guide from the prosthesis manufacturer. Axially loaded lateral radiographs were made to measure the tibiotalar ratio (TTR) preoperatively and postoperatively. Specimens were prepared for gait simulation and mounted into the robotic gait simulator. Foot bone kinematics and plantar pressures were measured for each alignment condition. Results: Posterior malalignment of the talar component decreased mean sagittal-plane range of motion (p ⩽ 0.0005) in the tibiotalar joint (by up to 3.9°) and in the first metatarsophalangeal joint (by up to 7.7°) and increased sagittal-plane range of motion (p ⩽ 0.0005) in the calcaneocuboid joint (by up to 2.0°). Posterior malalignment increased mean transverse-plane range of motion (p ⩽ 0.0005 and p = 0.012) in the tibiotalar joint (by up to 2.3°) and in the calcaneocuboid joint (by 2.3°). Posterior malalignment decreased mean peak plantar pressures (p = 0.001 and p = 0.013) under the hallux and the first metatarsal (by up to 82.1 and 110.1 kPa, respectively) and increased (p = 0.012 and p = 0.0006) peak plantar pressures under the third metatarsal and the hindfoot (by 23.0 and 47.8 kPa, respectively). Anterior malalignment decreased (p = 0.0006) mean hindfoot peak plantar pressure (by 127.7 kPa). Anterior and posterior malalignments shifted center of pressure laterally during early and late stance. The TTR weakly to moderately correlated with range-of-motion changes in the tibiotalar, calcaneocuboid, and first metatarsophalangeal joints (r 2 ⩽ 0.39) and weakly correlated with plantar pressure changes under the hindfoot, the first metatarsal, and the hallux (r 2 ⩽ 0.15). Conclusions: Anterior and posterior malalignments of the talar component altered foot bone kinematics and plantar pressures. Mild malalignments produced fewer significant differences than moderate and extreme malalignments. A greater number of significant differences were found for posterior malalignments than for anterior. The TTR weakly to moderately correlated with changes in range of motion and plantar pressures. Clinical Relevance: The observed changes in range of motion and plantar pressures may explain why malaligned ankle arthroplasties are associated with unfavorable clinical outcomes and poor prosthesis longevity. Posterior malalignments may produce worse clinical outcomes than anterior malalignments.